Integrating global diversity values into primary school social studies modules in the Merdeka Curriculum - Pambudhi, Tegar; Sapriya, Sapriya; Abdul Hakam, Kama; Sopandi, Wahyu (Jurnal Bidang Pendidikan Dasar, 2026)
This study investigates how global diversity values are incorporated into Social Studies (IPS) modules in Indonesian primary schools under the Merdeka Curriculum. Global diversity, part of the Pancasila Student Profile, stresses cultural pluralism, inclusive interaction, and equal participation in multicultural settings. Using a descriptive qualitative approach, the research involved document analysis, interviews with school leaders and teachers, and classroom observations, analyzed through Miles and Huberman’s (2014) interactive model. The study discovered that schools vary in their effectiveness in integrating global diversity values through themes such as "Cultural and Social Diversity" and "Global Interactions." Effective strategies included contextual content, reflective discussions, and project-based learning. Success factors were teacher competence, leadership, and community involvement, while challenges included limited training, time, and assessment tools. The Merdeka Curriculum offers a solid base for global citizenship education, but systematic teacher development and better module design are needed for consistent, meaningful integration.